K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 12 2021

\(=\dfrac{x^2-9-x^2+9}{x\left(x-3\right)}=0\)

25 tháng 12 2021

\(\dfrac{x+3}{x}-\dfrac{x}{x-3}+\dfrac{9}{x^2-3x}=\dfrac{x^2-9-x^2+9}{x\left(x-3\right)}=\dfrac{0}{x\left(x-3\right)}=0\)

17 tháng 10 2018

Câu 1 :

\(2x^2\left(3x-5x^3\right)+10x^5-5x^3\)

\(=6x^3-10x^5+10x^5-5x^3\)

\(=x^3\)

Câu 2 :

\(\left(x+3\right)\left(x^2-3x+9\right)+\left(x-9\right)\left(x+3\right)\)

\(=x^3+3^3+\left(x^2+3x-9x-27\right)\)

\(=x^3+27+x^2-6x-27\)

\(=x^3+x^2-6x\)

\(\frac{\left(x-3\right)^3}{3x^2}:\frac{x^2-6x+9}{6x}\)

\(=\frac{\left(x-3\right)^3}{3x^2}.\frac{6x}{\left(x-3\right)^2}\)

\(=\frac{2\left(x-3\right)}{x}\)

\(=\frac{2x-6}{x}\)

#H

3 tháng 8 2021

Trả lời:

\(\frac{\left(x-3\right)^3}{3x^2}:\frac{x^2-6x+9}{6x}\)

\(=\frac{\left(x-3\right)^3}{3x^2}.\frac{6x}{x^2-6x+9}\)

\(=\frac{\left(x-3\right)^3}{3x^2}.\frac{6x}{\left(x-3\right)^2}\)

\(=\frac{\left(x-3\right)^3.6x}{3x^2.\left(x-3\right)^2}\)

\(=\frac{2\left(x-3\right)}{x}\)

27 tháng 7 2016

\(\left(x^2-9\right)^2-\left(x+3\right)\left(x-3\right)\left(x^2+9\right)=\left(x-3\right)^2\left(x+3\right)^2-\left(x+3\right)\left(x-3\right)\left(x^2+9\right)\)

\(=\left(x-3\right)\left(x+3\right)\left[\left(x-3\right)\left(x+3\right)-x^2+9\right]=\left(x-3\right)\left(x+3\right)\left[x^2-9-x^2-9\right]=\left(x-3\right)\left(x+3\right)\cdot\left(-18\right)\)

\(=-18\left(x+3\right)\left(x-3\right)\)

9 tháng 9 2017

a,       x- 9 - x2 - 3x + 10 = 1 - 3x

19 tháng 12 2018

Thực hiện phép tính

a,  6x3y5z : 3xy3z=2x2y2

b,  \(\frac{3x+6}{x+2}+\frac{2x+4}{x+2}\)

\(=\frac{3\left(x+2\right)}{x+2}+\frac{2\left(x+2\right)}{x+2}\)

=3+2=5

a: \(=\dfrac{4x-8+2x+4-8}{\left(x-2\right)\left(x+2\right)}=\dfrac{6x-12}{\left(x-2\right)\left(x+2\right)}=\dfrac{6}{x+2}\)

b: \(=\dfrac{-x+7x-4}{3x-2}=\dfrac{6x-4}{3x-2}=2\)

c: \(=\dfrac{x}{2x+1}-\dfrac{1}{\left(2x+1\right)\left(2x-1\right)}-\dfrac{\left(x-2\right)}{2x-1}\)

\(=\dfrac{2x^2-x-1-\left(x-2\right)\left(2x+1\right)}{\left(2x+1\right)\left(2x-1\right)}\)

\(=\dfrac{2x^2-x-1-2x^2-x+4x+2}{\left(2x+1\right)\left(2x-1\right)}\)

\(=\dfrac{2x+1}{\left(2x+1\right)\left(2x-1\right)}=\dfrac{1}{2x-1}\)

d: \(=\dfrac{5}{2x-3}+\dfrac{2}{2x+3}+\dfrac{2x-33}{4x^2-99}\)

\(=\dfrac{10x+15+4x-6+2x-33}{\left(2x-3\right)\left(2x+3\right)}=\dfrac{16x-24}{\left(2x-3\right)\left(2x+3\right)}=\dfrac{8}{2x+3}\)

3 tháng 6 2019

\(3x\left(x-1\right)^2-2x\left(x+3\right)\left(x-3\right)+4x\left(x-4\right)\)

\(=3x\left(x^2-2x+1\right)-2x\left(x^2-9\right)+4x^2-16x\)

\(=3x^3-6x^2+3x-2x^3+18x+4x^2-16x\)

\(=\left(3x^3-2x^3\right)+\left(4x^2-6x^2\right)+\left(3x-16x\right)\)

\(=x^3-2x^2-13x\)